The Stability of the Fixed Wings Unmanned Aircraft Using the PID Method at KRTI 2019 - Pramudya Wisnujati; Son Ali Akbar (Universitas Ahmad Dahlan, 2023)
This study designed a UAV with an unmanned aircraft type with a Fixed Wings model that can perform the PID tunning process manually using the FBWA flight mode. An unmanned aircraft with the Fixed Wings type is designed to perform PID Roll tuning based on altitude and flight speed using the trial and error method increases the Proll value of 0.06 x 2 until the oscillation disappears and the final value of Proll is reduced by 50%. For the Iroll value, the increase in the value made is 0.1 x 2, increase it until it is sufficient and the final value of Iroll is reduced by 50%. For the Droll value, increase the value of 0.004 x 2 until the oscillation disappears and the final value of the Droll is reduced by 50%.